A risk-stratified approach to the management of high-grade T1 bladder cancer. Issue 6 (November 2018) - Mannas, Miles P.; Lee, Taeweon; Nykopp, Timo K.; Costa, Jose Batista da; Black, Peter C.
Abstract : Purpose of review: A bladder-preserving approach for high-grade nonmuscle invasive bladder cancer that has invaded the lamina propria (T1HG) may result in increased recurrence, progression, and even death from bladder cancer in some patients. Initial radical cystectomy does have increased cancer-specific survival (CSS), but represents significant overtreatment for many patients. An evidence-based, risk-stratified approach is required to select patients for immediate radical cystectomy in order to improve CSS. Recent findings: A restaging transurethral resection aids in optimal staging and treatment of T1HG. Intravesical Bacillus Calmette-Guerin induction followed by 3 years of maintenance is the standard adjuvant management. However, when very high-risk (hydronephrosis, abnormal bimanual examination, variant histology, lymphovascular invasion, or residual disease on re-resection, and Bacillus Calmette-Guerin failure or early recurrence) or multiple high-risk factors (concomitant CIS, size >3 cm, multifocality, unfavorable tumor location, extensive lamina propria invasion, and elderly) are present, the risk of progression often outweighs the risk associated with radical cystectomy. In these cases, an immediate radical cystectomy likely provides an improved opportunity for cure compared to a bladder-preserving strategy. Summary: In order to increase the CSS of patients diagnosed with T1HG bladder cancer, an aggressive approach may benefit those with increased risk of progression.